Adding ecology into phylogeography: ecological niche models and phylogeography in tandem reveals the demographic history of the subalpine warbler complex. Issue 2 (3rd April 2019) - Perktaş, Utku; De Silva, Thilina N.; Quintero, Esther; Tavşanoğlu, Çağatay
ABSTRACT: Capsule: This study documents evidence of interglacial refugia during the Last Interglacial for birds in the Mediterranean region, and emphasizes the importance of the Last Interglacial on the geographic distribution and genetic structure of Mediterranean species. Aims: We focused on the historical biogeography of the subalpine warbler complex: Subalpine Warbler Sylvia cantillans and Moltoni's Warbler Sylvia subalpina ; we tested if this Mediterranean bird complex shared a similar demographic fate as the present-day widespread species in the temperate zones of Europe, through the late Quaternary glacial-interglacial cycles. Methods: An ecological niche model was developed to predict the geographic distribution of the subalpine warblers under the past (the Last Interglacial and the Last Glacial Maximum) and the present bioclimatic conditions. Additionally, Bayesian Skyline Plot analysis was used to assess effective population size changes over the history of the subalpine warbler complex. Results: During the Last Glacial Maximum, the subalpine warblers almost reached their current distribution in the Mediterranean region; yet, unlike the widespread temperate bird species, they survived the Last Interglacial in allopatric refugia in the Mediterranean region. Conclusion: A unique biogeographic pattern was revealed, indicating the importance of the Last Interglacial on current distributional patterns and demographic histories of common bird species in the Mediterranean region. This study suggests that Mediterranean biogeography is far more complex than previously assumed, and so deserves further study and more attention.